The Relationship Between Learning Outcomes in the Basic Pattern Construction Course and Learning Outcomes in the Computer Pattern Making Course - Nashira Isnandita; Irmayanti Irmayanti (Jurnal Penelitian Pendidikan, 2026)
Digital transformation in the fashion industry has accelerated the use of Computer-Aided Design (CAD) technology in garment pattern-making processes. This development requires fashion education students to master both manual and digital technical skills. This study aims to analyze the relationship between learning outcomes in the basic pattern construction course and students' learning outcomes in the computer pattern making course. This study employed a quantitative approach with an ex post facto research design. The study population consisted of 81 students from the Fashion Education Study Program, Universitas Negeri Semarang, class of 2023. The sampling technique used was total sampling, so that all members of the population were included as research participants. Data analysis was carried out using descriptive statistical analysis, normality test, homogeneity test, and Spearman rank correlation analysis with the assistance of IBM SPSS Statistics version 26. The results showed that the correlation coefficient between students' learning outcomes in the basic fashion pattern construction course and computer pattern making was 0.210 with a significance value of 0.060 (ρ > 0.05). These findings indicate that a high level of mastery of manual pattern-making skills does not always correspond to better learning outcomes in computer-based digital pattern-making courses. Therefore, more integrative learning strategies are needed to bridge the conceptual and procedural gap between manual pattern construction and its application in CAD-based digital pattern systems.